TRENDS AND VARIABILITY IN EVAPOTRANSPIRATION AT JUNAGADH, GUJARAT - Chhodavadia, S. K. (Innovare Journal of Agricultural Sciences, 2016)
Email: skchhodavadia@gmail.com Abstract Evapotranspiration demands and trends were analyzed for Junagadh region in western Gujarat by assessing reference evapotranspiration (ETo), energy balance and aerodynamic components for 32 years (1984-2015). The analysis indicated multiple trends in annual EToand annual aerodynamic component of ETo. In the first half of the study period, a clear decreasing trend was observed with 2002 and 2004 years having low ETovalues.Later, the ETo started increasing andthe highest EToof 1522 mm was observed in the years 1987,which was drought year. Energy balance component has shown increasing trend with the increasing in temperature and sunshine hours. The trends in 32 years average ETovalues indicated toincreased in kharif season while the EToreduction in rabiseason. Present study highlights the necessary to understand ETo of the region before planning and management. Key words: Weather parameters, Climate change, Penman-Monteith, ETo, Gujarat